Leadership Transformation in the Digital Age: Implications for Employee Performance and Engagement in Modern Organizations - Hanuna Shafariah; Akmil Asril; Redjeki Agoestyowati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
Leadership transformation in the digital era has become a key element in determining the success of modern organizations. This study aims to analyze the effect of digital leadership on employee performance and engagement. A quantitative approach with descriptive and explanatory survey design was used to collect data from 200 respondents in the technology, banking, and education sectors. The research instrument was a 5-point Likert scale questionnaire measuring technological adaptability, support for innovation, policy flexibility, and information transparency as dimensions of digital leadership. The results of the linear regression analysis showed that digital leadership has a significant positive effect on employee performance with a regression coefficient of 0.45 (p <0.01) and on employee engagement with a coefficient of 0.38 (p <0.05). The coefficients of determination were 0.52 and 0.46, respectively, indicating that most of the variation in employee performance and engagement can be explained by digital leadership. These findings emphasize the importance of technological adaptability and innovation support in creating a productive and collaborative work environment. The practical implications of this study include digital leadership training, the implementation of flexible work policies, and the increase of information transparency to strengthen the relationship between leaders and employees. In conclusion, effective digital leadership increases productivity and strengthens employee commitment and motivation, making it an important strategy for creating sustainable organizational competitiveness in the digital era.